Distribution and speciation of heavy metals in two different sludge composite conditioning and deep dewatering processes. Issue 124 (30th November 2015) - Li, Chao; Zhang, Shinan; Yang, Jiakuan; Shi, Yafei; Yu, Wenbo; Liang, Sha; Song, Jian; Xu, Qi; Chen, Ye; Hu, Jingping; Li, Ye; Yang, Changzhu
Abstract : Pilot-scale sewage sludge dewatering experiments were conducted using two composite conditioners: FeCl3 + lime (Fe-lime) and Fenton's reagents + red mud (Fenton-RM). Abstract : Pilot-scale sewage sludge dewatering experiments were conducted using two composite conditioners: FeCl3 + lime (Fe-lime) and Fenton's reagents + red mud (Fenton-RM). Mass balance analysis was performed on Cu, Zn, Pb, Cd, and Cr during the conditioning and dewatering processes to investigate their transformation and distribution. Speciation of heavy metals was also investigated by the Tessier sequential extraction method. Results show that (1) most of the heavy metals were retained in the solid cake during the dewatering process, especially Cu and Cr; (2) in the sludge cakes, more than 87 wt% of Cu and Cr existed in organic bound and residual forms, and the contents of the bioavailable fractions (exchangeable, carbonate bound and Fe–Mn oxides bound form) for Zn, Pb, and Cd were larger in the Fenton-RM system than those in the Fe-lime system; (3) the main factors affecting the distributions of these heavy metals are pH and chemical speciation in two conditioning processes. Generally, heavy metal concentrations in filtrate and dewatered sludge cakes in both systems were below the corresponding standards, and heavy metals in the dewatered sludge cake could be more effectively immobilized in the Fe-lime system than in that of the Fenton-RM system.